Attitudes Toward, and Use of, Vibrators in China. Issue 1 (2nd January 2018) - Jing, Shen; Lay, Alixe; Weis, Laura; Furnham, Adrian
ABSTRACT: The current study examined the relationship between traditional masculine traits and attitudes toward vibrator use, actual vibrator use, and frequency of vibrator use in China. In all, 235 Chinese females aged between 16 and 58 years completed a questionnaire regarding attitudes toward, and personal use of, vibrators. The results showed a positive association between masculine traits and attitudes toward women's vibrator use, attitudes toward vibrator use and actual vibrator use, as well as frequency of vibrator use. The findings revealed an indirect path in which masculinity influences actual and frequency of vibrator use through attitudes toward women's vibrator use. Limitations and implications of the study are discussed.